QUANTITATIVE AND QUALITATIVE TEST OF THE FECAL SAMPLE FROM SUMATRAN ELEPHANT (Elephas maximus sumatranus) - Indriati, Winda; Yustian, Indra; Setiawan, Arum (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Sumatran Elephants (Elephas maximus sumatranus) is one of the endemic Sumatran fauna that is protected by Indonesia Law. The Remnant Forest of Acacia District Penyabungan in the landscape of Padang Sugihan is one of the elephantâ€™s habitats in South Sumatra. Habitat degradation and fragmentation, poaching and conflicts become the major threats for the elephant population. Genetic study is one of the efforts to establish a conservation policy. It is necessary to test the quantitative and qualitative of DNA, at the extractions stage from fecal samples, in order to get the standard results on DNA concentration which will be analyzed later. The method used is through direct observation as the initial survey to determine the sampling location. Fecal samples were preserved in absolute ethanol at -20Â°C.Â The extraction process was carried out using the Quick-DNATM Fecal/Soil Microbe Miniprep Kit. Samples were tested quantitatively using a Nanodrop Thermo Scientific, with the expectation that the concentration results were considered to be 1.6-1.8 and continued with the qualitative test of DNA through electrophoresis gel agarose and UV Transilluminator. Of the 20 samples, only 12 samples showed positive results (there were DNA bands). The results of this quantitative and qualitative test could be used to determine a viable sample to be used as a product in the genetic analysis stage of Sumatran Elephants in the Remnant Forest of Acacia South Sumatra.